2006
DOI: 10.2134/agronj2006.0022
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing of Nitrogen Stress in Creeping Bentgrass

Abstract: Development of a remote sensing system that can reliably identify nutrient deficiencies may reduce time spent sampling turfgrass areas and allow for site‐specific applications of fertilizers. The objectives of this research were to evaluate the use of a ground‐based remote sensing system and partial least‐squares (PLS) regression to predict the N concentration, biomass production, chlorophyll content, and visual quality of creeping bentgrass (Agrostis stolonifera L. ‘Penncross’) growing under varying N rates, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 28 publications
4
32
0
Order By: Relevance
“…This enables the quantification of chemical attributes of the leaves. For example, spectral absorption features have been used successfully to estimate foliar N concentration (Jain et al, 2007;Kruse et al, 2006;Tarpley et al, 2000;White et al, 2000;Zhao et al, 2005). White et al (2000) selected the 2028 nm wavelength to form a model of estimating vegetation leaf N concentration from in situ spectroscopic data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This enables the quantification of chemical attributes of the leaves. For example, spectral absorption features have been used successfully to estimate foliar N concentration (Jain et al, 2007;Kruse et al, 2006;Tarpley et al, 2000;White et al, 2000;Zhao et al, 2005). White et al (2000) selected the 2028 nm wavelength to form a model of estimating vegetation leaf N concentration from in situ spectroscopic data.…”
Section: Introductionmentioning
confidence: 99%
“…Read et al (2002) found the highest correlation between cotton leaf N content and reflectance at a ratio of reflectance between 700 and 710 nm. Furthermore, Kruse et al (2006) indicated that reflectance ratio 706-760 nm was the best index of predicting leaf N concentration of bentgrass. Additionally, Zhao et al (2005) who investigated the relationship between leaf N concentration and reflectance of sorghum crops reported that firstorder derivatives of the reflectance in the red edge centered at 730 or 740 nm yielded r 2 of 0.73.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al (2008) found that leaf N concentration was significantly associated with NDVI (R 2 = 0.36-0.47) when both were measured at the panicle formation stage for rice grown under three to five rates of N fertilizer ranging from 0 to 200 kg ha -1 . Kruse et al (2006) observed that N concentration in plant biomass related to NDVI (R 2 = 0.23-0.63) of creeping bentgrass grown under three N rates of 0, 12.2 and 24.4 kg ha -1 when both biomass N and NDVI were measured simultaneously during the growing season.…”
Section: Discussionmentioning
confidence: 98%
“…In the ecosystems of the floodplains, the relationship between heavy metal concentration and chlorophyll content is much more complex. Kruse et al (2006) showed the positive relationship between nitrogen status and the chlorophyll content in plants. In contrast, Horler et al (1983) reported that heavy metal treated plants contained lower chlorophyll concentrations than healthy plants.…”
Section: Introductionmentioning
confidence: 96%
“…Clevers et al (2004) stated that grasslands with a higher biomass level grew in soils with a high organic matter and soil moisture content. Ackermann et al (2010) and Kruse et al (2006) showed that there was no simple relationship between soil heavy metal content and heavy metal concentration in plants. Sites with high accumulation rates of contaminants like heavy metals largely vary in nutrient content and water supply.…”
Section: Introductionmentioning
confidence: 99%